2021
DOI: 10.1097/md.0000000000027002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical efficacy of robotic right colectomy and laparoscopic right colectomy for right colon tumor

Abstract: Background: The purpose of this study was to compare the clinical efficacy of robotic right colectomy (RRC) and laparoscopic right colectomy (LRC) in the treatment of right colon tumor.Methods: We systematically searched PubMed, Web of science, EMBASE ClinicalTrials.gov and Cochrane Central Register for studies (studies published between January 2011 and June 2020). The included studies compared the clinical efficacy of RRC and LRC in the treatment of right colon tumor, and analyzed the perioperative data.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The study concluded that RRC was associated with a greater number of harvested lymph nodes (weighted MD [WMD] 1.47; P = 0.05), reduced blood loss (WMD -13.43; P = 0.0003), lower rate of conversion to open surgery (OR 0.30; P < 0.0001), but with a higher operative duration (WMD 65.20; P < 0.00001) when compared to LRC. No major differences were observed between the two approaches regarding bowel function recovery, length of hospitalization, reoperation rates, complication rates, mortality rates, wound infection, and anastomotic leakage [18].…”
Section: Literature Reviewmentioning
confidence: 88%
“…The study concluded that RRC was associated with a greater number of harvested lymph nodes (weighted MD [WMD] 1.47; P = 0.05), reduced blood loss (WMD -13.43; P = 0.0003), lower rate of conversion to open surgery (OR 0.30; P < 0.0001), but with a higher operative duration (WMD 65.20; P < 0.00001) when compared to LRC. No major differences were observed between the two approaches regarding bowel function recovery, length of hospitalization, reoperation rates, complication rates, mortality rates, wound infection, and anastomotic leakage [18].…”
Section: Literature Reviewmentioning
confidence: 88%
“…Recent meta-analyses published in 2021 by Zhu et al. [ 11 ] and Kowalewski et al. [ 12 ] and in 2019 by Rausa et al.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ]. All authors highlighted the significantly higher costs of the robotic procedure in comparison to laparoscopic surgery [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ]. Interestingly, only one department in the current study stated that they stopped robotic surgery due to higher costs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, laparoscopy is considered the standard of care for right-sided colonic cancer resection [18][19][20], and the implementation of robotic surgery is underway [21,22]. These MIS approaches are technically more demanding, especially if the ileocolonic anastomosis is performed intracorporeally, but widespread evidence supports that the surgical outcomes are improved compared to open surgery [12,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, laparoscopy is considered the standard of care for right‐sided colonic cancer resection [18–20], and the implementation of robotic surgery is underway [21, 22]. These MIS approaches are technically more demanding, especially if the ileocolonic anastomosis is performed intracorporeally, but widespread evidence supports that the surgical outcomes are improved compared to open surgery [12, 23–25]. Recently, Sweigert et al [26] compared prolonged minimally‐invasive (laparoscopic and robotic) right colectomies (having an operation duration between 165 and 319 min) with shorter open procedures (97–164 min), and showed that, despite the longer OT, MIS was associated with lower overall morbidity rate, anastomotic leak, surgical site infections and shorter hospital stay, confirming that the benefits of MIS were maintained also in long‐lasting procedures.…”
Section: Introductionmentioning
confidence: 99%